Combined surgical and endovascular treatment of extensive thoracic aortic aneurysm - Brát, Radim; Dočekal, Bohumil; Jursa, Radovan (Journal of cardiovascular surgery, 2006)
IM: Patients with extensive aneurysm involving ascending aorta, aortic arch and descending aorta are usually treated by sequential operations. For these patients we can also use combined surgical and endovascular treatment. The experience with this procedure published in the literature is very limited. We report our experience in the ''elephant trunk'' technique followed by an endovascular stent-grafting of the descending thoracic aorta in a small group of three consecutive patients with extensive thoracic aortic aneurysm. METHODS: Three consecutive patients with extensive thoracic aortic aneurysm or chronic dissection underwent combined surgical and endovascular treatment between January and December 2004. The procedure was carried out as a two-stage procedure. During the first stage aortic arch was replaced using the elephant-trunk'' method and during the second stage the stentgrafting of the descending aorta was performed. RESULTS: All three patients were treated successfully. There was no death, no endoleak and no permanent neurological deficit. One patient had a transient paraparesis. In all patients the spiral CT demonstrated excellent technical result without endoleak and with thrombosis of the paraprosthetic space. CONCLUSIONS: We can conclude, that the combined surgical and endovascular treatment of extensive thoracic aortic aneurysm is a feasible method which could reduce mortality and morbidity. In our institution the elephant trunk technique followed by an endovascular stent-grafting of the descending aorta is the preferred method of treatment in patients with extensive thoracic aortic aneurysm involving ascending aorta, aortic arch and descending aorta.
Keywords: lidé středního věku; kombinovaná terapie; Treatment Outcome; Male; Financing, Organized; dospělí; Aortic Aneurysm, Thoracic; cévy - implantace protéz; aneurysma hrudní aorty; lidé; senioři; Anastomosis, Surgical; stenty; Aged; disekce aorty; anastomóza chirurgická; ženské pohlaví; výsledek terapie; angioplastika; Angioplasty; polyethylentereftaláty; Adult; Aortic Dissection; mužské pohlaví; Combined Modality Therapy; Polyethylene Terephthalates; financování organizované; Stents; Middle Aged; Humans; Blood Vessel Prosthesis Implantation; Female